External context in individual placement and support implementation: a scoping review with abductive thematic analysis - Jaakko Harkko; Noora Sipilä; Hilla Nordquist; Tea Lallukka; Kaija Appelqvist‐Schmidlechner; Michael Donnelly; Anne Kouvonen (2023)
Abstract Background Context including the external context may considerably affect the adoption, implementation, sustainment, and scale-up of evidence-based practices. We investigated external contextual features by conducting a scoping review of empirical research regarding the implementation of an evidence-based psychiatric or mental health vocational rehabilitation service called Individual Placement and Support (IPS). Methods The protocol for the scoping review was registered with the Open Science Framework. We used the methodology by Joanna Briggs Institute for conducting the scoping review and reported it according to the PRISMA-ScR checklist. We searched 12 databases for research regarding ‘Individual Placement and Support’ or ‘Evidence-Based Supported Employment’. We retained peer-reviewed empirical studies investigating external contextual factors and their impact on IPS implementation outcomes. We extracted data from the eligible articles and conducted descriptive and thematic analyses. Results Fifty-nine original research papers met our eligibility requirements and were retained after reviewing 1124 titles and abstracts and 119 full texts. The analysis generated two main themes: (1) external contextual determinants of service delivery and (2) external systems influencing the evidence-to-practice process. The first main theme encompassed policies and laws, financing, and administratively instituted support resources, and organizational arrangements associated with external stakeholders that may facilitate or hinder the local implementation. The second main theme comprised strategies and actions used by different stakeholders to facilitate implementation locally or scale-up efforts at a system level. Discussion Our scoping review illustrates the important role that external contextual factors play and how they may facilitate or hinder the implementation and scale-up of the IPS model across mental health services in different countries. Consideration of these factors by decision-makers in mental health and welfare services, planners, providers, and practitioners is likely to facilitate the development of effective strategies for bridging the evidence-practice gap in implementing the EBPs. Finally, the scoping review identified gaps in knowledge and offered suggestions for future research. Trial registration Open Science Framework